2023
DOI: 10.1128/spectrum.00269-23
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Adenovirus Quantification with a Droplet Digital Polymerase Chain Reaction (ddPCR) Assay

Abstract: Measuring viral load using droplet digital PCR (ddPCR) is an absolute quantification approach that can facilitate comparability between different laboratories. This approach could prove valuable in studies that focus on the clinical utility of quantification. In this study, we evaluate a human adenovirus (HAdV) ddPCR assay and study the relationship between viral loads and outcomes after HAdV respiratory infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 27 publications
1
3
2
Order By: Relevance
“…Admissions and the need for supplemental oxygen were less likely in patients infected with HAdV-B3 when compared to patients infected with other types, an observation that did not reach statistical significance. The age group and percentage of admissions observed in our study for patients infected with HAdV-non-B3 genotypes were consistent with what we reported for HAdV infections in the time frame of 2020–2022 when HAdV-C predominated ( 8 ). Older age and immunosuppression were the top two variables associated with increased likelihood of admissions with HAdV.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Admissions and the need for supplemental oxygen were less likely in patients infected with HAdV-B3 when compared to patients infected with other types, an observation that did not reach statistical significance. The age group and percentage of admissions observed in our study for patients infected with HAdV-non-B3 genotypes were consistent with what we reported for HAdV infections in the time frame of 2020–2022 when HAdV-C predominated ( 8 ). Older age and immunosuppression were the top two variables associated with increased likelihood of admissions with HAdV.…”
Section: Discussionsupporting
confidence: 91%
“…Although higher viral loads in respiratory samples can be associated with acute infections, when comparing HAdV-B3 samples to non-B3 types collected within the first 7 days of symptoms, HAdV-B3 was associated with higher viral loads. Interestingly, in a prior study, we did not detect any significant differences in viral loads between samples from patients infected with different HAdV genotypes ( 8 ). The predominant genotypes in our prior study included HAdV-C1, C2, and C5 ( 8 ).…”
Section: Discussioncontrasting
confidence: 52%
See 3 more Smart Citations